Efektivitas Nutrichick Gel® dalam mempertahankan bobot badan day-old chick selama masa transportasi dengan jarak tempuh yang berbeda - Putra, Hamdika Yendri; Sampurno, Nugroho; Alfiansyah, Fiqhi; Nugraha, Pratama Gusti; Idayanto, Sugeng (Current Biomedicine, 2024)
Background: Stress during the transportation period can cause a decrease in day-old chicken (DOC) body weight, which will increase maintenance costs to achieve harvest weight targets. Objective: The research aimed to examine the effect of Nutrichick Gel® product on maintaining body weight of DOC during transportation with different distances. Method: A total of 816 DOC from a hatchery in Sukabumi, West Java, were divided into 4 groups: S+Nutrichick, S-Nutrichick, P+Nutrichick, and P-Nutrichick, with 204 heads in each group. The S+Nutrichick and P+Nutrichick groups received 0.5 mL of Nutrichick Gel® per head, while the S-Nutrichick and P-Nutrichick groups were not given any supplements. The S+Nutrichick and S-Nutrichick groups were transported to Sukoharjo (518 km, ±8 hours; short distance) and the P+Nutrichick and P-Nutrichick groups were transported to Padang (1350 km, ±36 hours; long distance). The difference in weight gain and uniformity was observed before and after transportation. Results: Nutrichick Gel® supplemented groups showed the increased body weight and uniformity percentages, with 0.78% and 4.88% for the S+Nutrichick group, and 4.14% and 2.81% for the P+Nutrichick groups, respectively. The control group without supplementation displayed the decreased body weight and uniformity percentages, with -1.66% and -2.77% for the S-Nutrichick groups and -7.34% and -9.21% for the P-Nutrichick groups, respectively. No DOC’s mortality was observed in all groups. Conclusion: Nutrichick Gel® supplementation could maintain the DOC's body weight during transportation. The longer the distance traveled, the higher the benefits obtained from the difference in body weight using Nutrichick Gel® supplementation.